Vorinostat enhances the cisplatin-mediated anticancer effects in small cell lung cancer cells. Issue 1 (December 2016) - Pan, Chun-Hao; Chang, Ying-Fang; Lee, Ming-Shuo; Wen, B-Chen; Ko, Jen-Chung; Liang, Sheng-Kai; Liang, Mei-Chih
Abstract Background Vorinostat, a histone deacetylase (HDAC) inhibitor, is a promising agent for cancer therapy. Combining vorinostat with cisplatin may relax the chromatin structure and facilitate the accessibility of cisplatin, thus enhancing its cytotoxicity. Studies have not yet investigated the effects of the combination of vorinostat and cisplatin on small cell lung cancer (SCLC). Methods We first assessed the efficacy of vorinostat with etoposide/cisplatin (EP; triple combination) and then investigated the effects of cotreatment with vorinostat and cisplatin on H209 and H146 SCLC cell lines. The anticancer effects of various combinations were determined in terms of cell viability, apoptosis, cell cycle distribution, and vorinostat-regulated proteins. We also evaluated the efficacy of vorinostat/cisplatin combination in H209 xenograft nude mice. Results Our data revealed that the triple combination engendered a significant reduction of cell viability and high apoptotic cell death. In addition, vorinostat combined with cisplatin enhanced cell growth inhibition, induced apoptosis, and promoted cell cycle arrest. We observed that the acetylation levels of histone H3 and α-tubulin were higher in combination treatments than in vorinostat treatment alone. Moreover, vorinostat reduced the expression of thymidylate synthase (TS), and TS remained inhibited after cotreament with cisplatin. Furthermore, an in vivo study revealed that the combination of vorinostat and cisplatin significantly inhibited tumor growth in xenograft nude mice (tumor growth inhibition T/C% = 20.5 %). Conclusions Combined treatments with vorinostat promote the cytotoxicity of cisplatin and induce the expression of vorinostat-regulated acetyl proteins, eventually enhancing antitumor effects in SCLC cell lines. Triple combinations with a low dosage of cisplatin demonstrate similar therapeutic effects. Such triple combinations, if applied clinically, may reduce the undesired adverse effects of cisplatin. The effects of the combination of vorinostat and cisplatin should be evaluated further before conducting clinical trials for SCLC treatment.